Evaluation of pain susceptibility by taking blood pressure in patients with infections: A prospective comparative study. Issue 31 (6th August 2021) - Eldin, Carole; Boudjema, Sophia; Meddeb, Line; Boyer, Laurent; Soriano, Christophe; Parola, Philippe; Lagier, Jean-Christophe; Stein, Andreas; Gouriet, Frédérique; Gautret, Philippe; Million, Matthieu; Raoult, Didier
Abstract : Abstract: Pain sensitization leading to polyalgia can be observed during infectious diseases. The blood pressure cuff-evoked pain threshold (BPCEPT) has been used in previous studies as a screening tool for fibromyalgia. We aimed to use the BPCEPT as a screening test for detecting pain sensitization in patients suffering from infectious diseases. We also investigated whether specific factors were associated with pain sensitization. We performed a prospective comparative study including all patients of our infectious diseases center in a 1-year period. We created a positive control group of patients suffering from fibromyalgia and a negative control group of "apparently healthy" patients consulting for vaccination. The blood pressure (BP) cuff was inflated until the patient signaled that they experienced pain, and this pressure value was noted. A total of 2355 patients were included. The positive control group had significantly lower values of the BPCEPT than all other groups. Among hospitalized patients with infectious diseases, a low BPCEPT was significantly associated with high temperature ( P  < .0001), older age ( P  = .002), being a woman ( P  = .004), high serum glutamic-oxaloacetic transaminase ( P  = .007), and high C reactive protein levels ( P  = .02). Moreover, in multivariate analysis, respiratory infection, meningitis, urinary tract infection, febrile neutropenia, and Q fever were independently associated with a low BPCEPT. A significant negative dynamic correlation between the BPCEPT and temperature was also observed ( P  < .001). We demonstrated for the first time in a large sample of patients that the BPCEPT method can be used to detect pain susceptibility. We observed a significant dynamic correlation between pain sensitization and temperature. Additionally, pain sensitization was associated with some diseases, suggesting that they trigger pain sensitivity. Abstract : Supplemental Digital Content is available in the text